Progress of autophagy on regulating adipocyte lipid metabolism and differentiation - ZHOU Ye, CHEN Shu-qin, JIN Yong, LI Li (Jichu yixue yu linchuang, 2020)
Disorders of lipid metabolism are closely related to the metabolic diseases such as obesity. Autophagy is the main process of host cells to clear and degrade cellular contents. Different autophagy types play different roles in processing lipids and interact with traditional lipase-mediated lipolysis pathways. Autophagy also plays an important role in regulating adipocyte differentiation. Mitophagy is a form of selective autophagy that can regulate the differentiation of adipocytes and maintain the balance of beige adipocytes, which can provide new ideas of targeted therapy to the prevention of obesity and other metabolic diseases.